Verification of THz genetic algorithm using a VNA - Fenlon, Vanessa J.; Cooke, Michael; Mayock, Jim; Gallant, Andrew; Balocco, Claudio (International Conference on Infrared, Millimeter, and Terahertz Waves (Print), 2021)
THz antennas have been designed using a bespoke genetic algorithm. A patch antenna designed using this technique was found to have a mean improvement of 7.58 dB on a reference patch between 0.1 THz and 5.0 THz. This paper presents the testing of this antenna between 0.8 THz and 1.0 THz and subsequent verification of the algorithm.